Efficacy and safety of fesoterodine 8 mg in subjects with overactive bladder after a suboptimal response to tolterodine ER. Issue 9 (4th June 2014) - Kaplan, S. A.; Cardozo, L.; Herschorn, S.; Grenabo, L.; Carlsson, M.; Arumi, D.; Crook, T. J.; Whelan, L.; Scholfield, D.; Ntanios, F.; the Assessment of Fesoterodine after Tolterodine ER (AFTER) Study Group
Summary Aims To assess fesoterodine 8 mg efficacy over time and vs. placebo in subjects with overactive bladder (OAB) who responded suboptimally to tolterodine extended release (ER) 4 mg. Methods In a 12‐week, double‐blind trial, subjects with self‐reported OAB symptoms for ≥ 6 months, mean of ≥ 8 micturitions and ≥ 2 to < 15 urgency urinary incontinence (UUI) episodes/24 h, and suboptimal response to tolterodine ER 4 mg (defined as ≤ 50% reduction in UUI episodes during 2‐week run‐in) were randomised to fesoterodine (4 mg for 1 week, 8 mg for 11 weeks) or placebo once daily. Change from baseline to week 12 in UUI episodes (primary end‐point) was analysed in step‐wise fashion: first, baseline vs. week 12 for fesoterodine; if significant, then change from baseline to week 12 for fesoterodine vs. placebo. Results By week 12, subjects receiving fesoterodine 8 mg had significantly greater improvement from baseline vs. placebo in UUI episodes, urgency episodes and scores on the Patient Perception of Bladder Control, Urgency Perception Scale and OAB Questionnaire Symptom Bother and Health‐Related Quality of Life scales and domains (all p < 0.05). 50% and 70% UUI responder rates were also significantly higher with fesoterodine 8 mg vs. placebo at week 12 (p < 0.05). Dry mouth (placebo, 4%, 12/301; fesoterodine, 16.6%, 51/308) and constipation (placebo, 1.3%, 4/301; fesoterodine, 3.9%, 12/308) were the most frequent adverse events. Conclusions Subjects who responded suboptimally to tolterodine ER 4 mg showed significant improvements in UUI and other OAB symptoms and patient‐reported outcomes, with good tolerability, during treatment with fesoterodine 8 mg vs. placebo.